Designing social equality architecture, aesthetics, and the perception of democracy - Gage, Mark Foster (Routledge, 2019)
"In Designing Social Equality, Mark Foster Gage proposes a dramatic realignment between aesthetic thought, politics, social equality, and the design of our physical world. By reconsidering historic concepts from aesthetic philosophy and weaving them with emerging intellectual positions from a variety of disciplines, he sets out to design a more encompassing social theory for how humanity perceives its very reality, and how it might begin to more justly define that reality through new ways of reconsidering the built environment."--